Judaism and the philosophy of religion - Shatz, David (Cambridge studies in religion, philosophy, and society, 2026)
"David Shatz offers a new and fresh approach to the field in a wide-ranging and engaging introduction to the analytic philosophy of religion from the perspective of Judaism"-- Provided by publisher